PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN - Mutmainnah, Mutmainnah; Puspitaningtyas, Zarah; Puspita, Yeni (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019DO - 10.24843/BSE.2019.v24.i01.p02, 2019)
Firm value is investor’s view on the company which is related with stock price that may foster a positive signal to open the investment opportunities. This research aims to determine the effect of dividend policy, investment decision, firm size and managerial ownership on firm value of consumer good industry sector at Indonesia Stock Exchange in 2013-2017. The sample is selected using purposive sampling method on 11 companies. Furthermore, the data is processed using multiple linear regression analysis. The Results of research showed that dividend policy and investment decision have significant positive effect on firm value. But firm size and managerial ownership have significant negative effect on firm value.